Macrophage global metabolomics identifies cholestenone as host/pathogen cometabolite present in human Mycobacterium tuberculosis infection - Chandra, Pallavi; Coullon, Heloise; Agarwal, Mansi; Goss, Charles W; Philips, Jennifer A (The Journal of clinical investigation, 2022)
Mycobacterium tuberculosis (M. tuberculosis) causes an enormous burden of disease worldwide. As a central aspect of its pathogenesis, M. tuberculosis grows in macrophages, and host and microbe influence each other's metabolism. To define the metabolic impact of M. tuberculosis infection, we performed global metabolic profiling of M. tuberculosis-infected macrophages. M. tuberculosis induced metabolic hallmarks of inflammatory macrophages and a prominent signature of cholesterol metabolism. We found that infected macrophages accumulate cholestenone, a mycobacterial-derived, oxidized derivative of cholesterol. We demonstrated that the accumulation of cholestenone in infected macrophages depended on the M. tuberculosis enzyme 3[beta]-hydroxysteroid dehydrogenase (3[beta]-Hsd) and correlated with pathogen burden. Because cholestenone is not a substantial human metabolite, we hypothesized it might be diagnostic of M. tuberculosis infection in clinical samples. Indeed, in 2 geographically distinct cohorts, sputum cholestenone levels distinguished subjects with tuberculosis (TB) from TB-negative controls who presented with TB-like symptoms. We also found country-specific detection of cholestenone in plasma samples from M. tuberculosis-infected subjects. While cholestenone was previously thought to be an intermediate required for cholesterol degradation by M. tuberculosis, we found that M. tuberculosis can utilize cholesterol for growth without making cholestenone. Thus, the accumulation of cholestenone in clinical samples suggests it has an alternative role in pathogenesis and could be a clinically useful biomarker of TB infection.